The psychostimulant modafinil facilitates water maze performance and augments synaptic potentiation in dentate gyrus (2010)
Modafinil is a psychostimulant drug used widely for the treatment of narcolepsy, which also has additional positive effects on cognition. Here, we investigate the effects of modafinil on behavioural performance and synaptic plasticity in rats. Improved acquisition in the water maze task was observed in animals that underwent chronic treatment with modafinil. We found that the distance traveled and escape latency were reduced after the first day in chronically-treated rats, compared to controls. Importantly, swim velocity was similar for both groups, excluding pharmacological effects on motor skills. We also found that modafinil increases synaptic plasticity in the dentate gyrus of urethane-anaesthetized rats; modafinil induced a robust augmentation of the population spike, evident after application of 2 bursts of 200 Hz high-frequency stimulation. Furthermore, the modafinil-dependent enhancement of postsynaptic potentials correlated selectively with theta rhythm augmentation. We propose that modafinil may facilitate hippocampal-associated spatial representation via increased theta-related hippocampal plasticity.